The serotonin transporter gene-linked polymorphic region (5-HTTLPR) and cortisol stress reactivity: a meta-analysis - Matthis Wankerl; Robert Miller; Tobias Stalder; Clemens Kirschbaum; Nina Alexander (European Journal of Psychotraumatology, 2012)
Background : Recent meta-analyses have stimulated an active debate on whether the serotonin transporter gene-linked polymorphic region (5-HTTLPR) is associated with an elevated vulnerability to psychiatric diseases on exposure to environmental adversity. As a potential mechanism explaining genotype-depended differences in stress sensitivity, altered stress-induced activation of the hypothalamus-pituitary-adrenal (HPA) axis has been investigated in several experimental studies, with most of the studies comprising small samples. Methods : We evaluated the association of 5-HTTLPR genotype and cortisol reactivity to acute psychosocial stress by applying a meta-analytical technique based on 11 relevant data sets (total N=1686), which were identified through a systematic literature search up to October 2011. Results : The present meta-analysis indicates a small (d=0.27), but significant association between 5-HTTLPR genotype and HPA-axis reactivity to acute psychosocial stress with homozygous carriers of the S allele displaying increased cortisol reactivity compared to individuals with the S/L and L/L genotype. The latter association was not further moderated by participants’ age, sex or the type of stressor. Formal testing revealed no evidence for a substantial selection or publication bias. Conclusions : Our meta-analytical results are consistent with a wide variety of experimental studies indicating a significant association between 5-HTTLPR genotype and intermediate phenotypes related to stress sensitivity. Future studies are needed to clarify the consistency of this effect and to further explore whether altered HPA-axis stress reactivity reflects a potential biological mechanism conveying an elevated risk for the development of stress-related disorders in S allele carriers.